2004
DOI: 10.2307/20159626
|View full text |Cite
|
Sign up to set email alerts
|

Partner Substitutability, Alliance Network Structure, and Firm Profitability in the Telecommunications Industry.

Abstract: MARTIN GARGIULO INSEADThis paper explores the effects of partner substitutability and alliance network structure on organizational profitability. Although firms are expected to benefit from the exclusive resources brought in by resource-rich, nonsubstitutable alliance partners, the costs of allying with such partners could offset those benefits. Analyzing alliances in the U.S. telecommunications industry, we show that a firm facing nonsubstitutable partners was better off when its alliances were embedded in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The capacity of the focal firms to appropriate value from the network depends not only on the attributes of networks, but also on the nature of the resource characteristics and the management of the relationship between these partners. A firm operating within a network of powerful partners may be unable to appropriate the benefits the network produces (Bae and Gargiulo, 2004). The prominent partners that contribute to joint value creation may also restrict the appropriation capacity of the focal firm, and consequently undermine its market performance.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The capacity of the focal firms to appropriate value from the network depends not only on the attributes of networks, but also on the nature of the resource characteristics and the management of the relationship between these partners. A firm operating within a network of powerful partners may be unable to appropriate the benefits the network produces (Bae and Gargiulo, 2004). The prominent partners that contribute to joint value creation may also restrict the appropriation capacity of the focal firm, and consequently undermine its market performance.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…In addition to reducing the cost between corporate investors and entrepreneurial ventures, geographic proximity can also enhance knowledge spillover and learning effects and offer strategic guidance to entrepreneurial ventures (Baum et al, 2022;Gargiulo, 2004). More specifically, geographic proximity between entrepreneurial ventures and corporate investors could enhance their interactions and strengthen their mutual trust, which can improve the quality and scope of information exchange (Kang, 2019).…”
Section: The Moderating Role Of Geographic Proximitymentioning
confidence: 99%
“…Several research findings provide conflicting findings on how the network impacts the industry. For example, few studies have proposed positive effects of networking in automotive, telecommunication, high-tech and manufacturing industries (Ahuja, 2000;Bae and Insead, 2004;Kotabe et al, 2003). However, several other studies have found conflicting results that networking either reduces or does not affect the performance of specific industries (Broekel and Boschma, 2011;Park et al, 2010;Rowley et al, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%